2021
DOI: 10.1016/j.heliyon.2021.e08149
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and proximate composition of the meat and shell of three snail species

Abstract: Meat is a vital source of nutrients for human wellbeing and health; however, recent studies suggest a decline in meat preference as a protein source due to some health problems associated with meat intake. This study evaluates the levels of essential elements (Mn, Mg, P, Ca, K, Cu, Na, Zn and Fe) and proximate composition (protein, fat, moisture, carbohydrate, fibre and ash) of three snail species namely; Achatina achatina, Achatina fulica and Archachatina marginata species from the Kumasi Central Market. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 42 publications
2
12
2
1
Order By: Relevance
“…Engmann et al, 2013 also obtained a protein composition of 82.96% for dried meat samples of A. achatina in Ghana. Protein has many other functions that include repairing worn-out tissues(Nkansah et al, 2021) and may be responsible for snail meat being used to enhance amputated limbs by traditional healers(Balogun, 2021). This study values were higher than the 7.93 obtained for moisture, 32.73% CP, but lower than the 9.17 and 1.59 obtained for ash and fat respectively byAgengo et al (2020).…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…Engmann et al, 2013 also obtained a protein composition of 82.96% for dried meat samples of A. achatina in Ghana. Protein has many other functions that include repairing worn-out tissues(Nkansah et al, 2021) and may be responsible for snail meat being used to enhance amputated limbs by traditional healers(Balogun, 2021). This study values were higher than the 7.93 obtained for moisture, 32.73% CP, but lower than the 9.17 and 1.59 obtained for ash and fat respectively byAgengo et al (2020).…”
mentioning
confidence: 49%
“…According to Oyegu et al, 2018, Jimoh et al, 2020, snail meat is high in protein, iron, calcium and phosphorus, but low in sodium, fat and cholesterol, and contains almost all the amino acids needed by man. The variations observed in the ash content from this study could be attributed to the different minerals and vitamins present in the test ingredients Nkansah et al, (2021)…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…According to estimates, 43,000 tons of snails were consumed globally in 2016, and 50,000 tons are expected to be consumed by the end of 2025 [ 3 ]. Snail meat has been reported to be rich in protein and have a low fat and cholesterol content that make it meet the demands of modern nutrition [ [4] , [5] , [6] ]. It has also been reported that snail meat is a valuable source of essential fatty acids, amino acids, and minerals [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Land snails are invertebrate animals, with soft bodies (meat) that are rich in protein and water (Adeyeye, Afolabi, 2004). The predominant species of snail found in sub-Saharan Africa are the Achatina achatina, Achatina fulica and Archachatina marginata (Apata et al, 2015;Nkansah et al, 2021). Fish is an aquatic animal that is rich in proteins and fats.…”
Section: Introductionmentioning
confidence: 99%